Pengembangan Media Pembelajaran Mobile Learning Berbasis Android pada Mata Pelajaran Informatika Fase E di Tingkat SMA - Aulia, Aniza Ulfa; Hendri, Nofri; Pratiwi, Rahmi; Kurnia, Reni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research is based on the low utilization of smartphone devices as effective learning media, as well as the limitations of time and supporting media in Informatics learning at SMAN 1 Lembah Gumanti. The purpose of this research is to develop mobile learning media based on Android to support the Informatics learning process in Phase E at the high school level. The research employs the Research and Development (R&D) method with the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate). Validation is conducted by material and media experts, while practicality and effectiveness tests involve students in grade X Phase E. The validation test data from the material aspect obtained an average score of 3.79 with the criteria 'Very Valid'. The validation results of the media aspect received a score of 3.00 from media expert 1, categorized as